Implementasi Kebijakan Penurunan Stunting di Kota Sukabumi - Saepudin, Dede Yusuf; Muksin, Nani Nurani; Nugraha, Imam; Adimiharja, Rochman (Fakultas Ilmu Administrasi Universitas Krisnadwipayana Jakarta, 2025)
Stunting is a serious health problem that has a direct impact on the quality of human resources. Sukabumi City is one of the areas that has not been free from the problem of stunting. With a fairly high prevalence rate, the Sukabumi City Government is committed to reducing the prevalence of stunting through various policies and programs that have been and are being implemented. This article aims to analyze the implementation of policies to reduce the prevalence of stunting in Sukabumi City. The results show that the Sukabumi City Government has collaborated with various institutions from the health, education and social sectors that are integrated in reducing the prevalence of stunting. This collaboration has created synergy between SKPD and the pentahelix elements within it, resulting in several program innovations both at the city and regional levels. In addition, it is supported by the availability of resources including human resources, budget resources, health facilities, and information systems that can support the implementation of the program optimally. From the various programs that have been rolled out, it has shown a good commitment from the policy implementers, but efforts to motivate and increase active participation from the community continue to be made. The Regional Government through the Sukabumi City Health Office in implementing the stunting prevalence reduction program, continues to be committed and motivated to reduce the stunting prevalence rate with the hope of achieving the specified prevalence reduction target.